Age Differences in the Relationship Between Outdoor Physical Activity and School Emotional Well-Being in Pre-Adolescents: A Stratified Correlation Analysis - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: Subjective well-being (SWB) in pre-adolescents declines with age due to rising school-related stress and boredom. Outdoor physical activity (PA) may mitigate these effects, yet age-specific associations remain understudied. This study investigated age differences in relationships between outdoor PA and school emotional well-being (stress and arguments) using multinational data. Methods: Cross-sectional secondary analysis of the International Survey of Children s Well-Being (ISCWeB) third wave (2017-2019) involved 128,184 pre-adolescents (mean age 10.24 years, SD 1.70; 49.56% boys) from 35 countries, stratified by age (8, 10, 12 years). Outdoor PA was assessed on a 0-6 frequency scale; stress and arguments on 0-10 scales, with 8-year-olds responses harmonized from 5-point emoticons. Descriptive statistics and stratified Spearman correlations were calculated (p < 0.05). Results: Outdoor PA peaked at age 10 (mean 3.17, SD 1.62), while stress varied with age (mean 3.99, SD 0.50 at 8 years; 4.20, SD 2.50 at 12 years). Very small associations emerged: Weak negative stress correlations (r = -0.02 to -0.07, p <= 0.045; r(2) < 0.005) across ages, alongside positive argument associations (r = 0.03-0.08, p < 0.001). Conclusions: Outdoor PA modestly associates with lower stress in older pre-adolescents but may be associated with elevated peer conflicts. This dual effect adds nuance to interventions, highlighting supervision needs. Age-tailored, supervised school interventions could optimize emotional benefits during late pre-adolescence.